NS5 Conservative Site Is Required for Zika Virus to Restrict the RIG-I Signaling - Li, Aixin; Wang, Wenbiao; Wang, Yingchong; Chen, Keli; Xiao, Feng; Hu, Dingwen; Hui, Lixia; Liu, Weiyong; Feng, Yuqian; Li, Geng; Tan, Qiuping; Liu, Yingle; et al. (Frontiers in Immunology, 2020)
During host-virus co-evolution, cells develop innate immune systems to inhibit virus invasion, while viruses employ strategies to suppress immune responses and maintain infection. Here we reveal that Zika virus (ZIKV), a re-emerging arbovirus causing public concerns and devastating complications, restricts host immune responses through a distinct mechanism. ZIKV nonstructural protein 5 (NS5) interacts with the host retinoic acid-inducible gene I (RIG-I), an essential signaling molecule for defending pathogen infections. NS5 subsequently represses K63-linked polyubiquitination of RIG-I, attenuates the phosphorylation and nuclear translocation of interferon regulatory factor 3 (IRF3), and inhibits the expression and production of interferon-β (IFN-β), and thereby restricting the RIG-I signaling pathway. Interestingly, we demonstrate that the methyltransferase (MTase) domain of NS5 is required for the repression of RIG-I ubiquitination, IRF3 activation, and IFN- production. Detailed studies further reveal that the conservative active site D146 of NS5 is critical for the suppression of the RIG-I signaling. Therefore, we uncover an essential role of NS5 conservative site D146 in ZIKV-mediated repression of innate immune system, illustrate a distinct mechanism by which ZIKV evades host immune responses, and discover a potential target for anti-viral infection.